LANDASAN FILSAFAT PENDIDIKAN ISLAM MUHAMMAD ABDUH - Sehat Sulthoni Dhalimunthe (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2010)
Abstract: Foundation of Muhammad ‘Abduh’s Philosophy of Islamic Education. This article attempts to elaborate four philosophical concepts used by Muhammad ‘Abduh in constructing his thought in Islamic education. Thesekey concepts constitute his views on man, society, knowledge and morale (akhlâq). In his capacity as a reformer, Muhammad ‘Abduh did not only explain and emphasize the interrelation of these concepts in education, but also emphasize man’s need to maintain his faith in God, as well as build interaction amongst man at social level. The writer argues that this synergic interaction can only be achieved by an effective means through Islamic Instrument. Kata Kunci: konsep manusia, hakikat masyarakat, ilmu pengetahuan, akhlak